Persuasive Communication Strategy of Village Family Planning Volunteers in Bergas, Semarang - Sutikna, Nana; Riksaning Ayu, Kilau; Pangestuti, Sri (KnE Social Sciences, 2023)
Village Family Planning, also known as Kampung KB, was formed by the Indonesian National Family Planning Coordinating Board (BKKBN). This study focused on the Kampung KB area in Bergas Semarang that grew from ‘primary’ to ‘developing.’ Since 2018, the progress is marked by the data on the increase in couples carrying out family planning. In September 2020, the number of fertile age couples (PUS) who already have two children but have not participated in family planning (TIAL) was as many as 43 couples. Meanwhile, the latest data in August 2022 showed a decline in TIAL of 9 couples. This study aimed to determine the persuasive communication strategies of family planning volunteers in Kampung KB Bergas, Semarang. Qualitative descriptive research methods and Elaboration Likelihood (ELM) theory were used to explain the persuasive communication strategies used by volunteers. The study results showed they used a persuasive communication strategy with a central route in ELM theory. In addition, the COVID-19 pandemic has become a persuasive communication strategy in the post-pandemic era with a fear appeal approach that encourages increased use of contraceptives - one of the family planning village programs. Keywords: COVID-19, elaboration likelihood, family planning village, fear appeals